Pediatric clinical engagement on menstrual health: a qualitative assessment - Sarah Combs; Bhavana Huliyar; Isabella Brocato; Samantha Hill; Samuel Master; Linda Fan; Chinwe Efuribe; David Bell; Marni Sommer (Frontiers in Adolescent Medicine, 2026)
Background Menstrual health is a critical component of overall health. The American College of Obstetricians and Gynecologists (ACOG) and the American Academy of Pediatrics (AAP) recommend routine menstrual health screening and care during pediatric visits, yet this topic remains under-addressed in clinical encounters. The study aimed to explore how a diverse group of pediatric-facing providers engage with menstrual health during the pediatric clinical encounter and to identify existing barriers and facilitators for integrating menstrual health into routine care. Materials and methods This qualitative research study included in-depth interviews ( N = 46) with pediatric-facing providers across four geographic regions of the United States. Providers were recruited from a range of states, practice settings, urban, suburban, and rural contexts. The interviews sought to understand engagement with the topic of menstrual health within the pediatric encounter, barriers and facilitators to the conversation, and procedures and content when obtaining the menstrual history. Thematic analysis was used to analyze the interview transcripts. Results Participants represented 22 states across the four major geographic regions of the United States, with an approximately even distribution across practice types. The sample consisted primarily of Medical Doctors (78%), but also included Doctors of Osteopathy, Nurse Practitioners, and Physician Assistants. Roughly half of participants practiced in urban centers, with the remainder divided between suburban and rural settings. Analysis yielded three central themes: (1) formal training and experiential learning shape provider engagement with menstrual health; (2) structural and relational factors influence the extent to which menstrual health is integrated into clinical encounters; and (3) biological, quality-of-life, and condition-specific menstrual health questions affect clinical care. Conclusion These findings have important implications for the clinical encounter, including potential policy and practice implications to facilitate increased inclusion of attention to menstrual health in pediatric care. Integrating menstrual health questions that address both biological and quality of life issues into the clinical encounter is vital to addressing patient menstrual health holistically.